Effect of method of seed bed preparation, mulching and time of planting on yam (Dioscorea rotundata) in Western Nigeri. In C.L.A. Leakey (Eds.), Proceedings of the Third Symposium of the International Society for Tropical Root Crops (p. 293-306) - Hahn, S.K.; Lal, R. (1977)
Mulching of yam seed beds reduced soil temperature and improved emergence, time of emergence, yield per hill and the total yield of Dioscorea rotundata yams on a sandy soil in Western Nigeria. Comparison of mounds with ridged and flat seed beds showed that these different treatments had no significant effect on tuber yield. Planting about six -weeks before the onset of the rains and the use of mulch is indicated as a good technique to obtain high yield.